Assessment of stress-strain distribution in flatfoot deformity (part 1) - Korolkov, Oleksandr; Rakhman, Paviel; Karpinsky, Mykhaylo; Shishka, Igor; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
In the last decade, there has been an increase in the number of patients of different ages with the pathology of the foot. Thus, the flatfoot, according to different authors, is from 35 to 50 % of the entire pathology of the feet in children and up to 75 % in adults. One of the modern methods of surgical treatment of flatfoot is subtalar arthroesis. However, the researchers did not agree on its effectiveness. Objective: to study the stress-strain state of the bone elements of the foot in the normal and with flatfoot deformity. Methods: to solve this problem, a finite-element foot model was constructed, consisting of heel, talus, n avicular a nd s phenoid b ones, a s w ell a s t ibial a nd peroneal fragments. The joint surfaces were modeled by elements with mechanical properties of the cartilaginous tissue. Results: it is established that for the foot model, the stress intensity in all bone elements is uniformly distributed and has values in the range from 0.1 to 1.7 MPa. The zone of increased stress level is located on the supporting surface of the heel bone, where their maximum value reaches 4.9 MPa. As a result of the study of the model, a stress level was revealed in all bone elements of the foot, especially on the supporting surface of the calcaneus (from 4.9 MPa in the norm to 7.2 MPa) and on the surfaces of the joint, on the scaphoid bone (from 0.6 MPa in the norm to 6.9 MPa with the FFD). The highest concentration of stresses is determined on the posterolateral part of the joint surface of the talus bone — from 1.0 MPa in the norm to 13.5 MPa. Conclusion: the increase and redistribution of stresses in the osteochondrium elements of the foot in case flatfoot deformity can be a trigger mechanism for the development of an unstable ankle joint and arthrosis phenomena in the joints of the foot.